'Well, in dentistry the dentist is always the boss': a multi-method exploration of which organisational characteristics of dental practices most influence the implementation of evidence-based guidance. Issue 8 (3rd August 2022) - Cassie, Heather; Treweek, Shaun; McKee, Lorna; Ramsay, Craig; Young, Linda; Clarkson, Jan
Abstract : Objective: To investigate which organisational characteristics of primary care dental practices influence the implementation of evidence-based guidance. Design: A multimethod study set within primary care dentistry in Scotland comprising: (1) Semistructured interviews with dental teams to inform development of a self-report questionnaire exploring the translation of guidance in primary care dentistry and (2) A questionnaire-based survey and case studies exploring which organisational characteristics influence knowledge translation. Results: Interview data identified three themes: leadership, communication and context. Survey data revealed compliance with recommendations from three topics of dental guidance to be variable, with only 41% (emergency dental care), 19% (oral health assessment and review) and 4% (drug prescribing) of respondents reporting full compliance. Analysis revealed no significant relationship between practice characteristics and compliance with emergency dental care or drug prescribing recommendations. Positive associations were observed between compliance with oral health assessment and review recommendations and having a practice manager, as well as with the type of treatment offered, with fully private practices more likely, and fully National Health Service practices less likely to comply, when compared with those offering a mixture of treatment. Synthesis of the data identified leadership and context as key drivers of guidance uptake. Conclusions: Evidence-based dental recommendations are not routinely translated into practice, with variable leadership and differing practice contexts being central to poor uptake. Guidelines should aim to tailor recommendations and implementation strategies to reflect the complexities and varying contexts that exist in primary care dentistry, thus facilitating the implementation of evidence-based guidance.